Accuracy of VarioGuide Frameless Stereotactic System Against Frame-Based Stereotaxy: Prospective, Randomized, Single-Center Study - Bradac, Ondrej; Steklacova, Anna; Nebrenska, Katerina; Vrana, Jiri; de Lacy, Patricia; Benes, Vladimir (World neurosurgery, 2017)
INTRODUCTION: Frameless stereotactic brain biopsy systems are widely used today. VarioGuide (VG) is a relatively novel frameless system. Its accuracy was studied in a laboratory setting but has not yet been studied in the clinical setting. The purpose of this study was to determine its accuracy and diagnostic yield and to compare this with frame-based (FB) stereotaxy. MATERIAL AND METHODS: Overall, 53 patients (33 males and 20 females, 60 ± 15 years old) were enrolled into this prospective, randomized, single-center study. Twenty-six patients were randomized into the FB group and 27 patients into the VG group. Real trajectory was pointed on intraoperative magnetic resonance. The distance of the targets and angle deviation between the planned and real trajectories were computed. The overall discomfort of the patient was subjectively assessed by the visual analog scale score. RESULTS: The median lesion volume was 5 mL (interquartile range [IQR]: 2-16 mL) (FB) and 16 mL (IQR: 2-27 mL) (VG), P = 0.133. The mean distance of the targets was 2.7 ± 1.1 mm (FB) and 2.9 ± 1.3 mm (VG), P = 0.456. Mean angle deviation was 2.6 ± 1.3 deg (FB) and 3.5 ± 2.1 deg (VG), P = 0.074. Diagnostic yield was 93% (25/27) in VG and 96% (25/26) in FB, P = 1.000. Mean operating time was 47 ± 26 minutes (FB) and 59 ± 31 minutes (VG), P = 0.140. One minor bleeding was encountered in the VG group. Overall patient discomfort was significantly higher in the FB group (visual analog scale score 2.5 ± 2.1 vs. 1.2 ± 0.6, P = 0,004). CONCLUSIONS: The VG system proved to be comparable in terms of the trajectory accuracy, rate of complications and diagnostic yield compared with the "gold standard" represented by the traditional FB stereotaxy for patients undergoing brain biopsy. VG is also better accepted by patients.
Keywords: senioři; diferenciální diagnóza; interpretace obrazu počítačem; Brain Neoplasms; Intraoperative magnetic resonance; Accuracy; Frame-based stereotaxy; design vybavení; Tomography, X-Ray Computed; Cohort Studies; odchylka pozorovatele; Middle Aged; Sensitivity and Specificity; mužské pohlaví; Biopsy; mozek; Adult; Equipment Design; kohortové studie; Neuronavigation; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Brain biopsy; ženské pohlaví; neuronavigace; Humans; zobrazování trojrozměrné; lidé středního věku; nádory mozku; Imaging, Three-Dimensional; senzitivita a specificita; Diagnosis, Differential; biopsie; Image Interpretation, Computer-Assisted; dospělí; Frameless stereotaxy; počítačová rentgenová tomografie; Aged; Female; Diagnostic yield; Observer Variation; lidé; Male; Clinical outcome